Anatomical Features Around Eustachian Tube in Eosinophilic Otitis Media With Eosinophilic Sinusitis. (1st June 2021) - Ohira, Shinya; Komori, Manabu; Matsui, Hidehito; Furuya, Hanae; Kajiwara, Riko; Matsuura, Kentaro; Wada, Kota
Abstract : Objectives/Hypothesis: This study investigated the relationships between anatomical findings around the eustachian tube (ET) and eosinophilic otitis media (EOM) accompanied by eosinophilic chronic rhinosinusitis (ECRS). Study Design: This study employed axial, coronal, sagittal and oblique computed tomography. Methods: Patients who underwent endoscopic sinus surgery at the Department of Otolaryngology, Toho University Medical Center Omori Hospital and were diagnosed with ECRS (106 patients) based on the Japanese Epidemiological Survey of Refractory Eosinophilic Chronic Rhinosinusitis study were included. Subsequently, the presence of EOM accompanied by ECRS in 212 ear sides was assessed, and preoperative sinus computed tomography was used to evaluate various anatomical findings, such as the development of the sphenoid sinus and mastoid cells at the apex of petrous bone, the angle and length of the ET, and the size of the tympanic orifice of the ET. The relationships between these anatomical findings and the presence of EOM were analyzed statistically. Results: EOM accompanied by ECRS was associated with a high peripheral blood eosinophil count and bronchial asthma. Among anatomical factors, the absence of peri‐ET cells or petrous apex cells, and a low angle and short length of the ET, were risk factors for the onset of EOM. Conclusion: Anatomical factors such as the absence of peri‐eustachian cells or petrous apex cells, and low angle or short length of the ET, are risk factors for the onset of EOM along with ECRS. Assessment of these factors may help in preventing the future onset or aggravation of EOM. Level of Evidence: 4 Laryngoscope, 131:E2689–E2695, 2021